2-Arylpropionic Acid Pyrazolamides as Cannabinoid CB2 Receptor Inverse Agonists Endowed with Anti-Inflammatory Properties - Daniela R. de Oliveira; Rodolfo C. Maia; Patrícia R. de Carvalho França; Patrícia D. Fernandes; Gisele Barbosa; Lídia M. Lima; Carlos A. Manssour Fraga (MDPI AG, 2022)
Among the most recent proposals regarding the mechanism of action of dipyrone, the modulation of cannabinoid receptors CB1 and CB2 appears to be a promising hypothesis. In this context, the present work describes a series of five novel pyrazolamides (7-11) designed as molecular hybrids of dipyrone metabolites and NSAIDs, such as ibuprofen and flurbiprofen. Target compounds were obtained in good overall yields (50-80%) by classical amide coupling between 4-aminoantipyrine and arylacetic or arylpropionic acids, followed in some cases by N-methylation of the amide group. The compounds presented good physicochemical properties in addition to stability to chemical (pH 2 and 7.4) and enzymatic (plasma esterases) hydrolysis and showed medium to high gastrointestinal and BBB permeabilities in the PAMPA assay. When subjected to functional testing on CB1- or CB2-transfected cells, compounds demonstrated an inverse agonist profile on CB2 receptors and the further characterization of compound LASSBio-2265 (11) revealed moderate binding affinity to CB2 receptor (Ki = 16 µM) with an EC50 = 0.36 µM (Emax = 63%). LASSBio-2265 (11) (at 1, 3, and 10 mg/kg p.o.) was investigated in the formalin test in mice and a remarkable analgesic activity in the late inflammatory phase was observed, suggesting it could be promising for the treatment of pain syndromes associated with chronic inflammatory diseases.